(untitled) (Canadian Journal of Counselling and Psychotherapy, 2020)
The present study aimed to use the theory of planned behaviour (TPB) to explain Black Canadians’ underutilization of mental health services. The sample consisted of 294 community-based Black Canadians (84.7% female, 13.6% male). Participants completed self-report measures of relevant factors such as attitudes toward help-seeking, stigma against mental illness, and cultural mistrust. Path analyses revealed that the TPB model fits the sample data. Results also showed that integrating relevant psychological and cultural variables improved the explanatory power and fit of the model. These results provide insight into critical factors to be addressed for improving mental health service utilization among Black Canadians.